2012
DOI: 10.3141/2308-03
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Link Covering and Node Covering Formulations of Detection Layout Problem

Abstract: The primary data input used in principal traffic models comes from origin–destination (O-D) trip matrices, which describe patterns of traffic behavior across a network. O-D matrices are a critical requirement in advanced traffic management or information systems that are supported by dynamic traffic assignment models. However, because O-D matrices are not directly observable, current practice adjusts an initial seed matrix from link flow counts that are provided by an existing layout of traffic-counting statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Notably, the AVI sensors are deployed following a layout strategy, whose details can be found in [9], to optimize the capturing of Bluetooth equipped vehicles and provide effective travel time measurements between AVI sensors. Various methods were tested in the referenced paper [4] depending on different values for the design factors, such as initial a priori OD estimates, and penetration rates of Bluetooth equipped vehicles.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the AVI sensors are deployed following a layout strategy, whose details can be found in [9], to optimize the capturing of Bluetooth equipped vehicles and provide effective travel time measurements between AVI sensors. Various methods were tested in the referenced paper [4] depending on different values for the design factors, such as initial a priori OD estimates, and penetration rates of Bluetooth equipped vehicles.…”
Section: Resultsmentioning
confidence: 99%
“…These factors lead to low quality OD estimates. Therefore, significant research efforts have been devoted to the problem of detector location layout, to find the most optimal number and detection locations to ensure the best and most reliable OD estimates, taking into account the observability conditions necessary for acceptable quality estimates (Castillo et al., ; Barceló et al., ).…”
Section: An Example Of This Methodological Approach: Understanding Momentioning
confidence: 99%
“…Barcelona's Central Business District (CBD) scenario consists of 2111 sections, 1227 nodes (grouped in intersections), 120 origin centroids, 130 destination centroids, and a total of 877 nonzero OD pairs. There are 116 links with loop detectors supplying flow and occupancies with a time resolution of 5 minutes, and 50 ICT devices (Bluetooth) located at intersections in accordance with a layout determined by the procedures in Barceló et al (2012). Figure 15 network has 57 origin centroids and 57 destination centroids, and 2800 intersections, as shown in Fig.…”
Section: Two Case Studiesmentioning
confidence: 99%
“…Notice that z includes possibly node based, point-to-point based and (partial) OD based measurements. Notably, when travel time measurement are included in the estimation method,Barceló et al (2012) show that a detection layout based on node covering instead of the usual link covering, provides richer and more sensitive data, as this layout captures higher flows and allow to exploit the identification of partial paths between detectors, as later in this paper will be shown in the case of Vitoria`s network. In-depth discussions/analyses on path flow estimators have been proposed by various authors, and a basic reference could be found inBell (1997).…”
mentioning
confidence: 86%
“…The simulation of the true scenario leads to almost 90% of the trips collected twice at least in the afternoon-peak demand scenarios, whic most likely used paths identified in a D proposed by Barceló et al (2012) retu travel times on these predefined and stor In terms of perturbation of the tru approach adopted for OD flow perturb regarding the characteristics of the surv world. Without loss of generality, for hypothesized in this paper.…”
Section: Selection Of Measurement Locations and Perturbation Of True mentioning
confidence: 99%